The Transmission of Chinese Medicine in Australia - Mary Garvey (PORTAL: Journal of Multidisciplinary International Studies, 2011)
The paper explores some of the issues concerning the transmission of Chinese medicine in Australia, its practitioner training and the future of Chinese medicine as a distinct medical discipline in the Australian context. In China over the last century Chinese medicine was overhauled in order to align it with the biomedical perspective prevalent in the West. These changes, in turn, had important consequences for the transmission of CM in Australia and the West. But while the biomedicalisation of CM has offered the path of least resistance, it has also lead to unworkable simplifications and methodological failures. The paper thus argues for a renewed access to the tradition’s primary sources in order to ally the distinctive features and methods of traditional practice with biomedicine, as an alternative to an outright integration into biomedical practice.